Συμβολή στην ερμηνεία των μικρασιατικών στοιχείων της τέχνης του δέκατου αιώνα στη Μάνη - Γκιολές, Νίκος (Δελτίο Κέντρου Μικρασιατικών Σπουδών, 1984)
Some features of the architecture and wallpainting of 10th century Byzantine churches in Mani (SE. Peloponnese), can be interpreted as «oriental ». These features are the following: 1) the double apsidal simple barrel-vaulted church of which the earliest dated monument is the church of Saint Panteleimon at Boularioi (991/2); 2) the masonry templon with arch opening. The above two features are found earlier in Cappadocia; 3) the large open porch in front of the west façade of the church of Asomatos above Ritta (10th century). This type of porch has only earlier parallel in Georgia (c. 600); 4) the dome with ribs which forms a cross of the same church. This type of dome-ribs also occurs in Georgia and Cappadocia; and 5) The stylistic and iconographie affinities between the wallpaintings of the 10th century in Mani and Cappadocia. These «oriental» features appear to have been imported into Mani from the East by members of the monastic movement of the 10th century. Many monks from Asia Minor were sent to Greece after the Byzantine victory over the Arabs (961) to reintroduce Christianity. Among these monks two became famous for their building activities, Saint Athanasios the Athonite and Saint Nicon the Metanoite. The latter was particularly active in the region of Laconia, where many tenth century buildings can be connected with his missionary activity.